Gamified virtual reality exposure therapy for adolescents with public speaking anxiety: a four-armed randomized controlled trial - Kahlon, Smiti; Lindner, Philip; Nordgreen, Tine (Frontiers in Virtual Reality, 2023)
Objective: Public Speaking Anxiety is highly prevalent among adolescents. However, few interventions have been developed specifically for this group. This four-armed randomized trial addressed the following research questions regarding interventions for adolescents with public speaking anxiety (PSA): 1) is Virtual Reality exposure therapy (VRET) more efficacious than online psychoeducation or waitlist, and 2) is VRET followed by online exposure therapy more efficacious than VRET alone or online psychoeducation followed by online exposure therapy? Methods: Adolescents, aged 13–16 with PSA were randomized to four groups: 1) VRET + no additional intervention (n = 20); 2) VRET + online exposure program (n = 20); 3) online psychoeducation program + exposure program (n = 40); or 4) waitlist (n = 20). Self-rated PSA symptoms served as primary outcome measure, with secondary outcomes covering other social anxiety symptoms. Results: Linear mixed models revealed that there was a significant difference in the decrease in PSA symptoms among adolescents receiving VRET compared with waiting list (p = 0.015), but no significant difference to the online psychoeducation program (p = 0.056). However, online psychoeducation program yielded smaller within-group effect sizes compared to VRET, d = 0.33 vs. d = 0.83 respectively. VRET + online exposure program had a significant decrease in PSA symptoms (p = 0.013), but no significant difference from VRET + no additional intervention or online psychoeducation + online exposure program. Symptom reduction remained stable at 3-month follow-up. Conclusion: The study shows the potential of delivering both gamified VRET as well as online psychoeducation and exposure programs as self-guided interventions for adolescents with PSA. Clinical trial registration:clinicaltrials.gov, identifier: NCT04396392